Freedom heroines : Susan B. Anthony, Elizabeth Cady Stanton, Jane Adams, Ida B. Wells, Alice Paul, Rosa Parks - Wishinsky, Frieda (Profiles (Scholastic Inc.), 2012)
A biography of six women activists in American history.